The Two Faces of Wheat - Wieser, Herbert; Koehler, Peter; Scherf, Katharina A. (Frontiers in Nutrition, 2020)
Wheat-based foods have been staple foods since about 10,000 years and constitute a major source of energy, dietary fiber and micronutrients for the world population. The role of wheat in our diet, however, has recently been scrutinized by pseudoscientific books and media reports promoting the overall impression that wheat consumption makes people sick, stupid, fat and addicted. Consequently, numerous consumers in Western countries have started to question their dietary habits related to wheat consumption and voluntarily decided to adopt a wheat-free diet without a medical diagnosis of any wheat-related disorder (WRD), such as celiac disease, wheat allergy or non-celiac gluten sensitivity. The aim of this review is to achieve an objective judgement of the positive aspects of wheat consumption as well as adverse effects for individuals suffering from WRDs. The first part presents wheat constituents and their positive nutritional value, in particular the consumption of products from wholegrain flours. The second part is focused on WRDs that affect predisposed individuals and can be treated with a gluten-free or -reduced diet. Based on all available scientific knowledge, wheat consumption is safe and healthy for the vast majority of people. There is no scientific evidence to support that the general population would benefit from a wheat-free diet.